KARAKTERISTIK GLULAM BAMBU APUS (Gigantochloa Apus) MENGGUNAKAN PEREKAT STYROFOAM BERDASARKAN JUMLAH DAN POLA PENYUSUNAN LAPISAN - Rezki Bela Putra; Pebriandi; Evi Sribudiani; Sonia Somadona (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2022)
Wood was a construction raw material that has long been developed before the advent of concrete and steel technology. The need of wood raw materials for construction was increasingly increasing while the availability of high quality wood was increasingly scarce. Therefore, in order to meet this an effort was needed to produce raw materials to replace wood, its was the development of laminated products or glulam made of bamboo apus (Gigantochloa apus) as structural and construction materials. Based on this, this study was conducted to determine the quality of glulam from Gigantochloa apus by using styrofoam adhesives based on number and pattern of layer arrangement. Sample was made of Gigantochloa apus with sized 30cm × 10cm arranged with the number and pattern of layer arrangement that have been determined. This study uses a complete randomized design combination with two treatments. Factor A was the number of layers (three layers, four layers and five layers) and factor B was the arrangement pattern (diagonal, horizontal and vertical). The physical and mechanical properties of glued laminated beams of Gigantochloa apus were tested based on JAS 234: 2003 Standard. The results showed that the quality of glulam met the physical properties of moisture content. While the mechanical properties of MOE and MOR did not meet the standards, so they did not be use as structural materials. Combination with horizontal, diagonal and horizontal lamina arrangement patterns gives the best results on the mechanical properties of glulam.